Long-Run Labour Income Distribution Dynamics: The Case of Chile 1990-2017 - Blundell, Richard; Corral, Vicente; Gómez-Lobo, Andrés (Estudios de Economía, 2025)
We analyse the long-run evolution of the labour income distribution for Chile. To this end, we use thirteen waves of the CASEN household socioeconomic survey from 1990 to 2017. During this period hourly earnings inequality measured by the Gini coefficient fell from 0.47 to 0.40. We use a RIF regression approach similar to Ferreira et al. (2021) for Brazil to decompose changes in average earnings and earnings inequality. We do not find observable variables that explain –either through an endowment effect or through a structural price change– a significant part of the decrease in hourly earnings inequality.